Inappropriate therapy of euvolemic hyponatremia, the most frequent type of hyponatremia in SARS-CoV-2 infection, is associated with increased mortality in COVID-19 patients - Pazos-Guerra, Mario; Ruiz-Sánchez, Jorge Gabriel; Pérez-Candel, Xavier; López-Nevado, Celia; Hernández-Olmeda, Fernando; Cuesta-Hernández, Martin; Martín-Sánchez, Javier; Calle-Pascual, Alfonso Luis; Runkle-de la Vega, Isabelle (Frontiers in Endocrinology, 2023)
Results: Age: 68 years ; 39.9% were female. Median admission SNa was 133 mmol/L [131][132][133][134]. Hyponatremia was mild (SNa 131-134 mmol/L) in 188/247 (76%). Volemia was available in 208/247 patients; 57.2% were euvolemic and the rest (42.8%) hypovolemic. Hyponatremia was left untreated in 154/247 (62.3%) patients. Admission therapy was not concordant with volemia in 43/84 (51.2%). In fact, the majority of treated euvolemic patients received incorrect therapy with isotonic saline (37/41, 90.2%,), whereas hypovolemics did not (p=0.001). The latter showing higher mortality rates than those receiving adequate or no therapy (36.7% vs. 19% respectively, p=0.023). The administration of isotonic saline to euvolemic hyponatremic subjects was independently associated with an elevation of inhospital mortality (Odds Ratio: 3.877, 95%; Confidence Interval: 1.25-12.03).Conclusion: Hyponatremia in COVID-19 is predominantly euvolemic. Isotonic saline infusion therapy in euvolemic hyponatremic COVID-19 patients can lead to an increased mortality rate. Thus, an exhaustive and precise volemic assessment of the hyponatremic patient with CAP, particularly when due to COVID-19, is mandatory before instauration of therapy, even when hyponatremia is mild.